2002
DOI: 10.1164/ajrccm.165.8.2103094
|View full text |Cite
|
Sign up to set email alerts
|

Erythromycin Inhibits Rhinovirus Infection in Cultured Human Tracheal Epithelial Cells

Abstract: To examine the effects of erythromycin on rhinovirus (RV) infection in airway epithelium, primary cultures of human tracheal epithelial cells were infected with the RV major subgroup, RV14, and the minor subgroup, RV2. Infection was confirmed by increases in viral RNA of the infected cells and viral titers of the supernatants. RV14 upregulated the expression of the mRNA and protein of intercellular adhesion molecule-1 (ICAM-1), the major RV receptor, and it increased the cytokine production. Erythromycin reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
149
4
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(175 citation statements)
references
References 41 publications
21
149
4
1
Order By: Relevance
“…Indeed, previous studies showed that augmentation of antiviral activity was not dependent on RV serotype [12]. In contrast to our findings, SUZUKI et al [10] showed decreased minor-type RV replication despite unmodified expression of LDLR by macrolide treatment. The discrepancy of our observations with these data might be explained by different macrolides used (azithromycin versus erythromycin), different duration of macrolide pre-treatment (24 h versus 3 days), different concentrations (50 versus 10 μM), different cell sources (bronchial versus tracheal epithelial cells) or different strains of minor-type RV used (RV1B versus RV2).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Indeed, previous studies showed that augmentation of antiviral activity was not dependent on RV serotype [12]. In contrast to our findings, SUZUKI et al [10] showed decreased minor-type RV replication despite unmodified expression of LDLR by macrolide treatment. The discrepancy of our observations with these data might be explained by different macrolides used (azithromycin versus erythromycin), different duration of macrolide pre-treatment (24 h versus 3 days), different concentrations (50 versus 10 μM), different cell sources (bronchial versus tracheal epithelial cells) or different strains of minor-type RV used (RV1B versus RV2).…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, we further demonstrated that azithromycin treatment had antiviral properties characterised by a seven-fold reduced RV1B replication in CF bronchial cells. Our findings confirm previous observations showing antiviral properties of macrolides such as azithromycin [12], erythromycin [10], clarithromycin [9] and bafilomycin A1 [11] in RV-infected airway epithelial cells. In addition, we observed that the decreased RV1B load after azithromycin treatment was not attributable to azithromycin-induced cytotoxicity.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…90% of rhinovirus serotypes gain entry into epithelial cells using ICAM-1 cellular receptors and blockade of these receptors in experimental studies have shown reduced infection severity (Turner, Wecker et al 1999), but further study is required before this treatment option becomes widely available. Macrolide antibiotics, Bafilomycin A1 and Erythromycin have been shown to inhibit ICAM-1 epithelial expression and hypothesis about their potential as anti-inflammatory agents have yet to be definitive, as clinical proof is either negative or inconclusive (Suzuki, Yamaya et al 2002).…”
Section: Prevention and Treatment For Respiratory Virusesmentioning
confidence: 99%